Segurança privada armada a bordo dos navios - Matos, Afonso Alves de (2022)
Piracy is an ongoing issue that plagues many, if not all, shipping security in high-risk areas is threatened, and as a result, the global supply chain is compromised. The measures adopted, to this date, by the parties involved, in order to mitigate this phenomenon, prove to be manifestly temporary. When governments realized that it would no longer be affordable to supply their own navies, progressively more nations began to allow, or not to hinder, private security on board their commercial ships, as a way to protect their ships. Bodies with competence in this area maintain, until this day, a disengaging position. Privately contracted armed security personnel on board ships is the prevailing reality. The present paper serves the purpose of analyzing the problems and vicissitudes of the Portuguese legal regime that regulates this activity, ascertaining its importance, comparing it with other nearby regimes, and its long-term viability.